2017
DOI: 10.1088/1361-6560/aa7fe6
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo skin dose simulation in intraoperative radiotherapy of breast cancer using spherical applicators

Abstract: • Intrabeam x-ray source and spherical applicators were simulated and skin dose was calculated. • Skin dose for constant skin to applicator distance strongly depends on applicator size. • Use of larger applicators generally results in higher skin dose. • The recommended 0.5-1 cm skin to applicator distance does not guarantee skin safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 30 publications
2
49
0
Order By: Relevance
“…In terms of source‐to‐source variations, dose rate measurements performed with another INTRABEAM source were found to differ by 15% to 5% as a function of depth in water, corresponding to a relative difference (i.e., the difference in the PDDs) of up to 10%. This is similar to previously reported source‐to‐source output variations . However, while source output variations (both day‐to‐day and source‐to‐source) would change the absolute doses reported in this work, the relative differences between the dose determination methods (i.e., TARGIT, Zeiss, CQ, film) would be unaffected.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of source‐to‐source variations, dose rate measurements performed with another INTRABEAM source were found to differ by 15% to 5% as a function of depth in water, corresponding to a relative difference (i.e., the difference in the PDDs) of up to 10%. This is similar to previously reported source‐to‐source output variations . However, while source output variations (both day‐to‐day and source‐to‐source) would change the absolute doses reported in this work, the relative differences between the dose determination methods (i.e., TARGIT, Zeiss, CQ, film) would be unaffected.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike previous studies, this study has a larger sample size of 15 XRSs and presents novel DDRs. While it is beyond the scope of this paper to speculate on the reasons for the observed differences, it has been previously suggested that the dose‐rate differences are attributed to the variability in target size, and small changes in other x‐ray generation structures (i.e., electron source) . Future work, in collaboration with Carl Zeiss Meditec, could correlate target thickness to the output characteristics.…”
Section: Discussionmentioning
confidence: 94%
“…Monte Carlo simulation of a breast phantom with realistic tissue compositions and skin layers, demonstrated that in vivo dose depends on the size of applicator as well as the amount of breast tissue between the applicator and the skin. In the study of Fogg et al., the ratios between average doses measured with TLDs at 5 mm and at 15 mm from the point of insertion were 1.47, 1.22, 1.24, and 1.11 for the 3.5, 4.0, 4.5, and 5.0 cm applicators, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that the dose rate is checked and, if necessary, readjusted before each treatment, these are unlikely to affect measured dose. Small differences in the various structures involved in the generation of x rays, including the electron source, the beam deflector as well as the gold target, such as between manufactured and ideal target thickness, could change photon spectra and doses between different sources, thus explaining a change of dose …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation